How public policies happen: Policy drift shapes policies for people with dyslexia in Iceland - Bjarnadóttir, Nanna Björk; Sigurgeirsdóttir, Sigurbjörg (Veftímaritið Stjórnmál og stjórnsýsla, 2013)
This study is about public policy-making for people with dyslexia in Iceland. Pupils with dyslexia are as a group the biggest group inside the educational system dealing with learning difficulties at school. In order to make sense of the current situation in this policy sector, the paper traces the processes by which policies for pupils with dyslexia at primary and secondary school levels in Iceland are made in the period 1990-2007. It identifies similarities and differences in the policy-making processes and compares the results with similarities and differences characterising the policy-making processes involved in merging the hospitals in Reykjavik in the 1990s. The aim is to bring out a better understanding about how public policies come about in general, but more specifically to bring new perspectives into the policy debate, in the hope it may encourage a new way of thinking about the ways policies for people with dyslexia are designed. The paper concludes that similar to the hospital reforms at the end of 1990s, the observed policy outcomes of educational policies for pupils with dyslexia in Iceland are a result of processes characterised by policy drift rather than stated public policy reforms. As a consequence, the growing fragmentation of the policy sector following the decentralisation in the 1990s, lack of coherent and cohesive community of professional expertise, and marketization of specialised services for pupils with dyslexia impede the formation of collective understanding inside the sector and the building up of a critical mass of experience and expertise in order to advance the scientific research and development necessary to effectively develop and design evidence-based policy responses to pupils with learning difficulties caused by dyslexia. Þessi grein fjallar um opinbera stefnumótun í málefnum nemenda með lesblindu á Íslandi. Talið er að stærsti hópur nemenda með námserfiðleika innan skólakerfisins séu nemendur með lesblindu. Til að átta sig á núverandi stöðu í þessum málaflokki, er ...